Historical Experiences And Modern Technologies In Teacher Training As Class Leaders (Journal of Pedagogical Inventions and Practices, 2025)
This article examines the role of the class teacher in the modern education system and their pedagogical competencies. The process of preparing future teachers as class supervisors is analyzed, along with the significance of innovative pedagogical technologies and digital approaches. Additionally, the historical development of the class leadership institution and its relevance today are discussed. The scientific conclusions presented in the article aim to develop recommendations for improving the effectiveness of the class teacher’s activities.